Pengaruh Sistem Layanan Jemput Zakat Dan Sistem Layanan Transfer Rekening Terhadap Tingkat Kepuasan Muzakki Pada Lazismu Kota Medan - Rizky Andika; Uswah Hasanah (Yayasan Rahmat Islamiyah, 2022)
This study aims to determine the effect of the zakat pickup service system and account transfer on the satisfaction of Muzaki Lazismu in Medan City. The research method used in this study is a quantitative method. The method in this study, the sample taken as many as 85 respondents. The technique used is Probability Sampling using the Simple Random Sampling method. The types of data used in this research are primary and secondary. The data collection technique used is a questionnaire. The data analysis technique is respondent descriptive, descriptive statistical analysis, classical assumption test, multiple regression test, and hypothesis testing processed by SPSS V 24.0 program. The results of this study indicate that the known value of the coefficient of determination (R2) is 0.169 or 16.9% while 83 ,1% is determined by other factors. Obtained tcount 3,069 with Sig. smaller than the t-value of 0.003 <0.05 for the X1 variable, then a t-table with Df = 56 (2.003) is obtained, so the t-value is 3.069 > 2.003, so it can be concluded: